Do Outside Directors Tell the Truth, the Whole Truth, and Nothing But the Truth When They Resign? - HUANG, Sterling Zhenrui (Institutional Knowledge at Singapore Management University, 2014)
This study examines the informativeness and credibility of the reasons cited by independent directors for resignation. Given that directors are privy to private information about the firm, they may resign in anticipation of future underperformance in order to limit potential damage to their reputation. We posit that directors have an economic incentive not to disclose the true reason for their resignation in order to protect their existing equity ownership, business relationships, and future directorship opportunities. Consistent with these conjectures, we find that the likelihood of resignation increases with reputation and weak future performance. Moreover, cases where ambiguous or unverifiable resignation reasons are given, or no reason is provided, are associated with poor recent and future financial and operating performance. Investors and analysts appear to at least partially understand and respond to such misrepresentations, as evidenced by an immediate negative and economically significant market reaction and downward forecast revisions. Complementary factors such as positive concurrent operating results and richer information environment seem to alleviate investor concerns and mitigate the negative reaction.